2023
DOI: 10.1186/s12957-023-03088-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of outcomes following loop electrosurgical excision and clinical features of patients with cervical high-grade squamous intraepithelial lesions with abnormal preoperative endocervical curettage

Abstract: Objective The purpose of this study was to identify the clinical characteristics of patients with high-grade squamous intraepithelial lesions (HSIL) with abnormal endocervical curettage (ECC) and to evaluate the efficacy of abnormal preoperative ECC in predicting recurrence after a loop electrosurgical excision procedure (LEEP). Methods We retrospectively analyzed a total of 210 cases of histological HSIL in female patients diagnosed using cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Feng's study showed that the detection rate of HSIL increased by 5% in patients who underwent colposcopy combined with ECC [37], and this detection rate increased with age [38]. At the same time, Feng's study confirmed that 2 years after the LEEP, the rate of recurrence in patients with ECC positivity was as high as 15.9% [37]. Our study revealed that ECC suggesting HSIL was an independent risk factor for uterine residual lesions.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Feng's study showed that the detection rate of HSIL increased by 5% in patients who underwent colposcopy combined with ECC [37], and this detection rate increased with age [38]. At the same time, Feng's study confirmed that 2 years after the LEEP, the rate of recurrence in patients with ECC positivity was as high as 15.9% [37]. Our study revealed that ECC suggesting HSIL was an independent risk factor for uterine residual lesions.…”
Section: Discussionsupporting
confidence: 63%
“…According to current when colposcopy is inadequate, ECC can be considered for nonpregnant patients [36]. Feng's study showed that the detection rate of HSIL increased by 5% in patients who underwent colposcopy combined with ECC [37], and this detection rate increased with age [38]. At the same time, Feng's study confirmed that 2 years after the LEEP, the rate of recurrence in patients with ECC positivity was as high as 15.9% [37].…”
Section: Discussionmentioning
confidence: 99%
“…HPV infection has been confirmed by multiple studies as an important predictive indicator for residual CIN lesions ( 5 , 22 , 23 ). In this study, the post-LEEP follow-up HPV infection status was closely related to the presence of residual CIN3 lesions after LEEP, and it can serve as an independent predictive indicator for residual lesions in CIN3 patients undergoing LEEP.…”
Section: Discussionmentioning
confidence: 84%
“…Other way, we do not rule out the possibility that this could be caused by collinearity between the variables, as well as potential selection bias and a relatively short follow-up period (18). HPV infection has been confirmed by multiple studies as an important predictive indicator for residual CIN lesions (5,22,23). In this study, the post-LEEP follow-up HPV infection status was closely related to the presence of residual CIN3 lesions after LEEP, and it can serve as an independent predictive indicator for residual lesions in CIN3 patients undergoing LEEP.…”
Section: Discussionmentioning
confidence: 99%